2019
DOI: 10.1039/c9em00136k
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of long-term temporal trends of POPs from co-located active and passive air monitoring networks in Europe

Abstract: Atmospheric concentrations and temporal trends of PCB 28 measured by co-located active (green) and passive (red) air sampling at the Birkenes monitoring station in Norway from 2004–2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…not one that is specic to a particular deployment, it may in fact be more transparent to not report volumetric air concentrations: the time-normalised sequestered amount has less uncertainty than the calculated (15, 47, 80, 120, 160, 200, 240, 280, 320 m) concentration, because the latter inherits the uncertainty of the SR. Several early PAS studies had reported spatial results in amount per sampler or amount per sampler per time, 29,280,390,391,432,433,448,469 but only recently has there been a reemergence of support for not necessarily reporting volumetric air concentrations. [514][515][516][517] This approach is clearly advisable when using a PAS whose SR under a given set of circumstances is not well established or even unknown. A good example is the study attaching a PAS to a gull, where it was entirely possible to compare the exposure of different birds using time-normalised sequestered amounts.…”
Section: G4 Spatial Variability In Indoor Air Concentrations and Inhmentioning
confidence: 99%
“…not one that is specic to a particular deployment, it may in fact be more transparent to not report volumetric air concentrations: the time-normalised sequestered amount has less uncertainty than the calculated (15, 47, 80, 120, 160, 200, 240, 280, 320 m) concentration, because the latter inherits the uncertainty of the SR. Several early PAS studies had reported spatial results in amount per sampler or amount per sampler per time, 29,280,390,391,432,433,448,469 but only recently has there been a reemergence of support for not necessarily reporting volumetric air concentrations. [514][515][516][517] This approach is clearly advisable when using a PAS whose SR under a given set of circumstances is not well established or even unknown. A good example is the study attaching a PAS to a gull, where it was entirely possible to compare the exposure of different birds using time-normalised sequestered amounts.…”
Section: G4 Spatial Variability In Indoor Air Concentrations and Inhmentioning
confidence: 99%
“…For PCBs and p,p'-DDE, the trends (annual changes per year) were in good agreement with the findings of Paper III. For α-HCH, annual changes were -10% and -9% and for γ-HCH, they were -11% and -12% at Råö and Pallas, respectively (Kalina et al, 2019). These rates of changes are almost twice as high as given in Paper III.…”
Section: Polychlorinated Biphenyls (Pcbs) and Organochlorine Pesticidmentioning
confidence: 53%
“…These declines were a very prominent feature in this material; of the studied 28 time series, all but one showed a s.s. decreasing trend. In a recent paper, Kalina et al (2019) published long-term trends (1996-2016/2018) of PCBs and HCHs based on the very same but extended data from Råö and Pallas. For PCBs and p,p'-DDE, the trends (annual changes per year) were in good agreement with the findings of Paper III.…”
Section: Polychlorinated Biphenyls (Pcbs) and Organochlorine Pesticidmentioning
confidence: 99%
See 2 more Smart Citations